Analysis of protein-protein interaction, transcriptional regulation and metabolic networks - Wagner, Andreas (Henry Stewart Talks, 2007)
Biological networks: small networks dedicated to a specific task and genome-scale networks, Protein interaction networks, The yeast two-hybrid assay and its limitations, Graph theory: degree distribution and correlation, characteristic path lengths and diameter, clustering coefficient, abundance of motifs and indicators of modularity, Measures of node and edge centrality, Affinity chromatography, Hypergraphs, Protein microarrays, Transcription regulation networks, Metabolic networks, Small-world networks, Flux balance analysis
Archived at 2018/05/31